E-Counseling : Mobile-Based Specialization System in Vocational Schools - Permana, Agus Aan Jiwa; Sudarma, Made; Darmayasa, Ngakan Nyoman (Darul Yasin Al Sys, 2024)
Many students who will continue their studies to the high school level are confused about choosing a major. This is because most students do not understand the majors at the vocational level, making it difficult for students to enter majors according to the talents and interests of each student. This research is a continuation of previous research that has developed web-based applications. With a majors specialization system using the Inventory Personal Survey Test model system which was built as a majors selection system at the SMK level, mobile access is needed to make it easier for students to access this service via an application on a smartphone.This system is designed using Android Studio and the database creation using MYSQL. The results of the specialization that has been carried out show that the system can be used to conduct online counseling and makes it easier for counselors to collect and analyze counseling results.